Nanoscale electrostatic gating of molecular transport through nuclear pore complexes as probed by scanning electrochemical microscopy. Issue 34 (12th July 2019) - Pathirathna, Pavithra; Balla, Ryan J.; Meng, Guanqun; Wei, Zemeng; Amemiya, Shigeru
Abstract : The nuclear pore complex (NPC) uses positive residues of amino acids to electrostatically regulate molecular transport through the peripheral route. Abstract : The nuclear pore complex (NPC) is a large protein nanopore that solely mediates molecular transport between the nucleus and cytoplasm of a eukaryotic cell. There is a long-standing consensus that selective transport barriers of the NPC are exclusively based on hydrophobic repeats of phenylalanine and glycine (FG) of nucleoporins. Herein, we reveal experimentally that charged residues of amino acids intermingled between FG repeats can modulate molecular transport through the NPC electrostatically and in a pathway-dependent manner. Specifically, we investigate the NPC of the Xenopus oocyte nucleus to find that excess positive charges of FG-rich nucleoporins slow down passive transport of a polycationic peptide, protamine, without affecting that of a polyanionic pentasaccharide, Arixtra, and small monovalent ions. Protamine transport is slower with a lower concentration of electrolytes in the transport media, where the Debye length becomes comparable to the size of water-filled spaces among the gel-like network of FG repeats. Slow protamine transport is not affected by the binding of a lectin, wheat germ agglutinin, to the peripheral route of the NPC, which is already blocked electrostatically by adjacent nucleoporins that have more cationic residues than anionic residues and even FG dipeptides. The permeability of NPCs to the probe ions is measured by scanning electrochemical microscopy using ion-selective tips based on liquid/liquid microinterfaces and is analysed by effective medium theory to determine the sizes of peripheral and central routes with distinct protamine permeability. Significantly, nanoscale electrostatic gating at the NPC can be relevant not only chemically and biologically, but also biomedically for efficient nuclear import of genetically therapeutic substances.